Analysis of DNA polymorphism and virulence in Philippine strains of Xanthomonas oryzae pv. oryzicola - Raymundo, A.K.; Briones, A.M.; Ardales, E.Y.; Perez, M.T.; Fernandez, L.C.; Leach, J.E.; Mew, T.W.; Ynalvez, M.A.; McLaren, C.G.; Nelson, R.J. (Scientific Societies, 1999)
Molecular tools were used to analyze the genetic diversity and population structure of Xanthomonas oryzae pv. oryzicola, the bacterial leaf streak pathogen of rice in the Philippines. Representative pathogen strains were selected and used to assess resistance in rice germplasm. A partial genomic library of X. oryzae pv. oryzicola was constructed, and a 459-bp clone containing the repetitive DNA element R41 was selected as a probe for restriction fragment length polymorphism (RFLP) analysis and sequenced. R41 shared 44% sequence homology with the putative transposase gene of IS1112, an insertion element cloned from X. oryzae pv. oryzae. Using R41 as a probe for RFLP analysis, 26 band profiles were discerned in a collection of 123 strains of X. oryzae pv. oryzicola. Analysis of PstI digestion patterns of DNA from the same collection resolved 36 haplotypes. Several clusters of strains were detected after grouping of data based on either pR41 as a probe or Pst1 digestion patterns. However, based on bootstrap analysis, the clusters were not robust. Genetic diversity was high for the entire collection as well as within spatially and temporally defined subsets of strains. Even a set of strains collected from a single site at a single time was highly diverse. Strains representing the different DNA types were inoculated to a set of diverserice cultivars. Consistent rice varietal groupings were obtained from disease reaction data, but there was no correlation between pathogen isolate cluster and host reaction across inoculation trials. Isozyme group I of rice, representing tropical japonica and javanica germplasm, is a promising source of resistance to bacterial leaf streak.